Effect of remelting power and remelting time on the morphological characteristics and mechanical properties of Fe-based clad layer. (February 2023) - Xi, Wenchao; Song, Boxue; Sun, Zhengyu; Ma, Zhelun; Yu, Tianbiao; Wang, Jun
Highlights: Laser remelting tests were conducted on the Fe-based clad layer under different remelting time and remelting power conditions. The morphological characteristics of the Fe-based clad layer after remelting under different remelting time and remelting power conditions were investigated. The microhardness of the Fe-based clad layer after remelting under different remelting time and remelting power conditions was investigated. The wear resistance, wear rate and wear mechanism of the Fe-based clad layer after remelting under different remelting time and remelting power conditions were investigated. When the remelting time is 1 and the remelting power is 650 W, the clad layer has high microhardness and outstanding wear resistance. Abstract: Laser remelting is a processing technique to improve the quality of forming. The remelting power and the remelting time are the key factors affecting its processing quality. Laser remelting tests were conducted on Fe-based clad layers with different remelting power and remelting time, and the morphological characteristics of each clad layer was investigated by laser microscopy. The microhardness, wear resistance and wear mechanism of each clad layer were investigated by Vickers microhardness tester and reciprocating friction and wear tester, respectively. The results show that an increase in remelting power or remelting time leads to a decrease in clad height and an increase in melting pool depth, clad width and dilution rate. When the remelting time is 1 and the remelting power is 650 W, the clad height is higher than that of YCF102 clad layer, although the melting pool depth, clad width and dilution rate of the clad layer are greater than that of YCF102 clad layer. In addition, an increase in remelting power or remelting times leads to a decrease in the microhardness of the clad layer and a deterioration in the wear resistance, which leads to an increase in the wear rate, but does not change the trend of microhardness, wear resistance and wear rate. Neither the increase in remelting power nor the remelting time leads to a change in the wear form, but causes the wear between the clad layer and the grinding ball to become more intense. The clad layer with 1 remelting time and 650 W remelting power has higher average microhardness and more outstanding wear resistance than the YCF102 clad layer.